2006
DOI: 10.1111/j.1365-294x.2006.02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of hybrid poplar (Populus trichocarpa× deltoides) interacting with forest tent caterpillars (Malacosoma disstria): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar

Abstract: As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar (Populus spp.) ESTs by focusing on herbivore- and elicitor-treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
177
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(186 citation statements)
references
References 127 publications
(177 reference statements)
8
177
0
1
Order By: Relevance
“…However, the recombinant UGT78M1 protein was not active with any anthocyanin, flavonol, or flavan-3-ol substrate that we tested, so its biochemical function remains undefined (Veljanovski and Constabel, 2013). The functions of the other UGT are also unknown; however, it is expressed in herbivore-stressed poplars (Ralph et al, 2006). A conspicuous group of down-regulated genes is annotated as encoding flavonoid 39-monooxygenase-like enzymes (i.e.…”
Section: Myb182 Is a Repressor That Reduces Pa And Anthocyanin Accumumentioning
confidence: 99%
“…However, the recombinant UGT78M1 protein was not active with any anthocyanin, flavonol, or flavan-3-ol substrate that we tested, so its biochemical function remains undefined (Veljanovski and Constabel, 2013). The functions of the other UGT are also unknown; however, it is expressed in herbivore-stressed poplars (Ralph et al, 2006). A conspicuous group of down-regulated genes is annotated as encoding flavonoid 39-monooxygenase-like enzymes (i.e.…”
Section: Myb182 Is a Repressor That Reduces Pa And Anthocyanin Accumumentioning
confidence: 99%
“…The third and most likely mode of volatile nitrile formation in planta is the oxidation of aldoximes by P450 enzymes of the CYP71 or CYP736 family as described for the biosynthesis of cyanogenic glycosides and camalexin (Bak et al, 1998b;Nafisi et al, 2007;Takos et al, 2011). The P. trichocarpa genome contains 25 CYP71 genes and six CYP736 genes (Nelson et al, 2008), and microarray analysis revealed that several of these genes were upregulated after herbivore feeding (Ralph et al, 2006). Therefore, they might play a role in herbivore-induced volatile nitrile formation in poplar.…”
Section: Cyp79d6v3-and Cyp79d7v2-produced Aldoximes Are Released Dirementioning
confidence: 99%
“…Similarly, third instars that fed in mesh bags on intact saplings also showed no effect of the high Table 4). It was assumed that AO activities were unaffected by larval feeding, since no evidence of AO induction by caterpillars has been observed in hybrid poplar (Major and Constabel 2006;Ralph et al 2006). Finally, the consumption and growth rates and nutritional indices (AD, ECD, and ECI) of fourth instars did not differ when contrasted between the control and AO-overexpressing genotypes (contrast P's≥ 0.690; Table 5).…”
Section: Resultsmentioning
confidence: 93%